2015
DOI: 10.5433/1679-0359.2015v36n6sup2p4589
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory responses and blood parameters of locally adapted ewes under natural weather conditions of Brazilian semiarid region

Abstract: The effect of the natural weather conditions on respiratory rate, rectal temperature and hematologic parameters such as glucose, total cholesterol, triacylglycerol, total protein, albumin, globulin, red blood cells, microhematocrit, mean corpuscular volume, serum triiodothyronine (T 3 ) and thyroxine (T 4 ) levels was evaluated in red (RMN) and white (WMN) coat colored Morada Nova ewes, of different class of body condition score (CBCS), during the dry (from july to december) and wet (from january to june) seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…These results could explain the low variability of RT and RR of animals among environmental conditions (from groups 1 to 5), possibly animals were acclimated to high radiation and air temperature in which they were exposed over the years. With regard to serum concentration of triiodothyronine (T 3 ) and thyroxine (T 4 ), the values for T 4 were higher in the most comfortable environmental conditions (group 1) and T 3 did not show differences among groups; similar results were reported by Costa et al (2015) that evaluated T 4 and T 3 in this breed and found that thyroid hormone secretion in dry season was lower than in rainy season.…”
Section: Resultssupporting
confidence: 73%
“…These results could explain the low variability of RT and RR of animals among environmental conditions (from groups 1 to 5), possibly animals were acclimated to high radiation and air temperature in which they were exposed over the years. With regard to serum concentration of triiodothyronine (T 3 ) and thyroxine (T 4 ), the values for T 4 were higher in the most comfortable environmental conditions (group 1) and T 3 did not show differences among groups; similar results were reported by Costa et al (2015) that evaluated T 4 and T 3 in this breed and found that thyroid hormone secretion in dry season was lower than in rainy season.…”
Section: Resultssupporting
confidence: 73%
“…In this result, higher efficiency of water metabolism appears to be involved (Pereira et al, 2014). Another study with Morada Nova breed indicated a good ability to cope with the climatic changes of the Brazilian semiarid region as they presented low RT and RR (38.59 ± 0.58 • C and 42.26 ± 8.96 mov min −1 ) during hot days (Costa et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…Thermal stress causes several changes in animal physiology, including a reduction in feed efficiency and intake, as well as disturbances in water, protein, energy, and mineral balance, limiting animal reproduction (Marai et al, 2007). Moreover, thermal stress causes a reduction in the production efficiency of animals (Dantas et al, 2015;Queiroz et al, 2015) and alterations in their rectal and skin temperatures; respiratory and heart rates (Furtado et al, 2017;Torres et al, 2017); and levels of thyroid, cortisol, and biochemical parameters such as total protein, albumin, globulin, cholesterol, triglycerides, urea, glucose, and gamma-glutamyltransferase (Costa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%